Moose browsing, understorey structure and plant species composition across spruce budworm‐induced forest edges. (27th January 2016) - Franklin, Caroline M.A.; Harper, Karen A.
Abstract: Question: To what extent do forest edges created by an insect outbreak influence patterns of moose browsing severity, understorey structure and species composition? Location: Balsam fir‐dominated boreal forest in Cape Breton Highlands National Park, Nova Scotia, CA. Methods: We sampled understorey vegetation (moose browsing damage, sapling density, plant composition, diversity) in contiguous 1‐m 2 quadrats along six 120‐m transects across the forested edges of insect outbreak areas. Patterns of each response variable across the disturbed area–forest gradient were determined using generalized additive mixed models. Randomization tests and wavelet analyses were used to estimate the extent of edge/forest influence and location of abrupt change along the edge‐to‐interior gradient, respectively. Results: Most saplings in the disturbed area were severely browsed and shorter than those in adjacent intact forest. Although moose preferred to browse on tall saplings, shorter saplings were severely browsed in the disturbed area. Compared to the forest, the disturbed area was characterized by more shade‐intolerant species, increased graminoid cover and reduced bryophyte cover. Distance of edge influence did not extend into the forest for almost all response variables. Abrupt changes in understorey vegetation occurred at various distances on both sides of the edge. Conclusions: Severe moose browsing in the disturbed area is preventing forest regeneration, resulting in the persistence of forest edges that would typically disappear after the collapse of an insect outbreak. Different assessments of the forest edge revealed different results; locations of abrupt change in understorey vegetation occurred even where plant communities were not significantly different than reference forest and disturbed areas. This study reveals that the combined effects of a small insect defoliator and a large ungulate can substantially affect landscape dynamics. Abstract : We examined patterns of moose browsing severity, understorey structure, and species composition across forest edges created by an insect outbreak. Forest regeneration has been hindered by severe damage from moose browsing, which also affected understorey vegetation. Severe moose browsing can ultimately maintain the boundary between disturbed areas and adjacent intact forests and therefore prolong the existence of forest edges.